Diversity of the Orthoptera at the Institut Teknologi Sumatera - Gres Maretta; Andy Darmawan; Dian Anggria Sari; Jeane Siswitasari Mulyana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
Orthoptera are important members of almost all terrestrial ecosystems, playing roles as both consumers and prey. Diversity refers to the various species found within a particular area. This study aims to determine the diversity index, dominance index, and evenness of the order Orthoptera at the Institut Teknologi Sumatera. Data collection on Orthoptera diversity was conducted and identified in the Zoology Laboratory at Institut Teknologi sumatera. Purposive sampling was used as the sampling technique, based on specific considerations. Observations were carried out at four locations around Institut Teknologi Sumatera and analyzed using diversity index, dominance index, and evenness index formulas. This study found 12 genera from the order Orthoptera. The diversity of Orthoptera at ITERA was categorized as moderate, with the diversity index (H’) values recorded as follows: Station I (1.879); Station II (1.765); Station III (1.626); and Station IV (1.843). No dominant individuals were found at any station. The evenness index at ITERA was categorized as high, with values of 0.784 at Station I; 0.767 at Station II; 0.678 at Station III; and 0.742 at Station IV, where Station I had the highest evenness value